JEJAK MIGRASI PENGHUNI PULAU MISOOL MASA PRASEJARAH - Fairyo, Klementin (BALAI ARKEOLOGI PAPUA, 2010)
Humans and the environment are interrelated and inseparable. Environment provides everything and humans able to manage and utilize.Based on archaeological remains on the misool island, be indicative of Austronesian migration to the misool island. Migration has been presenting a new culture in the form of rock art, pottery and building stone